Integration of socio-cultural digital teaching materials to enhance problem-solving and self-efficacy in elementary school mathematics - Nurlaela Nurlaela; Slamet Arifin; Siti Faizah (Universitas Papua, 2026)
This study developed and evaluated socio-cultural digital teaching materials for elementary mathematics and examined their validity, practicality, and effectiveness in improving students’ problem solving and self-efficacy. We employed a Research & Development design (Borg & Gall; 7 modified stages). A one-group pretest–posttest field try-out was conducted with Grade-5 students (n = 45). Instruments included a Polya-based problem-solving test and a self-efficacy questionnaire (5-point Likert); expert validation covered content, media, and language. Analyses comprised descriptive statistics, Shapiro–Wilk, paired t-test, N-Gain, effect size (Cohen’s dz), reliability (Cronbach’s α) and inter-rater agreement (Cohen’s κ), and Pearson correlation. Findings indicate very high validity (mean 91.1%) and high practicality (teachers 90.2%; students 88.0%; on-task observation 86.4%). Problem-solving performance rose from 55.3 (SD 11.2) to 76.8 (SD 10.1) with N-Gain = 0.48 (moderate), t(44) = 8.75; p < .001; dz = 1.30; the largest gains appeared in understand and look back. Self-efficacy increased from 3.10 (SD 0.52) to 3.78 (SD 0.49) with t(44) = 7.36; p < .001; dz = 1.10. Changes in self-efficacy correlated moderately and positively with problem-solving N-Gain (r = 0.41; p = 0.005). The results support the combined use of local cultural contexts, multimedia-learning principles, and Polya-based strategy scaffolding as a feasible and impactful approach to strengthening mathematical competence and self-belief in elementary students.